Dual Regulation of Host TRAIP Post-translation and Nuclear/Plasma Distribution by Porcine Reproductive and Respiratory Syndrome Virus Non-structural Protein 1α Promotes Viral Proliferation - Shi, Peidian; Su, Yanxin; Li, Ruiqiao; Zhang, Lei; Chen, Chen; Zhang, Lilin; Faaberg, Kay; Huang, Jinhai (Frontiers in Immunology, 2018)
In this study, we show that porcine reproductive and respiratory syndrome virus (PRRSV) non-structural protein 1α (nsp1α) facilitates PRRSV escape from innate immune by modulating nuclear to cytoplasmic translocation and distribution ratio of TRAIP to promote virus proliferation. Mechanistically, TRAIP interacts with PRRSV nsp1α via its K205 site, while NSP1α decreases the SUMOylation and K48 ubiquitination independent of the TRAIP interaction K205 site. Modulation of the dual modification of TRAIP by PRRSV nsp1α results in over-enrichment of TRAIP in the cytoplasm. Enrichment of nsp1α-induced cytoplasmic TRAIP in turn leads to excessive K48 ubiquitination and degradation of serine/threonine-protein kinase (TBK1), thereby antagonizing TBK1-IRF3-IFN signaling. This study proposes a novel mechanism by which PRRSV utilizes host proteins to regulate innate immunity. Findings from this study provides novel perspective to advance our understanding in the pathogenesis of PRRSV.